2020
DOI: 10.2478/jccm-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamical Assessment of Inflammatory Biomarkers in Predicting the Outcome of Septic Patients and the Response to Antimicrobial Therapy

Abstract: Aims:To evaluate the kinetics of inflammatory biomarkers in septic patients in order to identify the most reliable predictor of unfavorable outcome. Methods: A prospective analysis of septic patients was performed. Median levels of neutrophil/lymphocyte count ratio, fibrinogen, C-reactive protein and procalcitonin were dynamically assessed and comparatively analyzed. Results: Seventy-seven patients were included. Descendent kinetic patterns were registered for all biomarkers, except C-reactive protein. At 24 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…However, the dynamics of fibrinogen were not investigated within these studies, although decrease of fibrinogen levels may be observed in patients with progression of sepsis or septic shock. The present study demonstrated decrease of fibrinogen levels in patients admitted with septic shock (median decrease 41% from day 1 to day 3), whereas fibrinogen levels remained stable in patients with sepsis without shock (median increase 7.5% from day 1 to day 3), which may be attributed to SIC-related fibrinogen consumption in patients with more advanced stages of sepsis [29]. The prognostic impact of fibrinogen dynamics was investigated within 60 septic patients with increased CRP levels (i.e.…”
Section: Discussionmentioning
confidence: 47%
“…However, the dynamics of fibrinogen were not investigated within these studies, although decrease of fibrinogen levels may be observed in patients with progression of sepsis or septic shock. The present study demonstrated decrease of fibrinogen levels in patients admitted with septic shock (median decrease 41% from day 1 to day 3), whereas fibrinogen levels remained stable in patients with sepsis without shock (median increase 7.5% from day 1 to day 3), which may be attributed to SIC-related fibrinogen consumption in patients with more advanced stages of sepsis [29]. The prognostic impact of fibrinogen dynamics was investigated within 60 septic patients with increased CRP levels (i.e.…”
Section: Discussionmentioning
confidence: 47%
“…Leaving clinical diagnosis away, in many situations the laboratory diagnostics (sepsis biomarkers) may represent a helpful tool to predict the positive diagnosis of sepsis and/or septic shock [2,3,6]. There are hundreds of biomarkers that could be potentially used for diagnosis and prognosis in septic patients [3]. However, few studies have evaluated the discriminative power of PCT, CRP, and SChE activity kinetics as predictors of survival outcome in patients admitted to the ICU with septic shock [2][3][4][5][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…There are hundreds of biomarkers that could be potentially used for diagnosis and prognosis in septic patients [3]. However, few studies have evaluated the discriminative power of PCT, CRP, and SChE activity kinetics as predictors of survival outcome in patients admitted to the ICU with septic shock [2][3][4][5][10][11][12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations